Rethinking Security in the Anthropocene: A Multidisciplinary Paradigm Shift in International Relations - Miswar, Syarifah Huswatun (Khwopa Journal, 2025)
This article examines how the Anthropocene epoch, characterized by profound human impacts on the environment, is reshaping the landscape of international security. The main objective of this research is to analyze the inadequacy of traditional, military-focused security paradigms in addressing the diverse and interconnected risks emerging in the Anthropocene, such as climate change, resource depletion, and pandemics. To achieve this, the study employs a multidisciplinary literature review, drawing on insights from environmental studies, security studies, and international relations theory to critically assess the limitations of conventional approaches and to explore alternative frameworks. The findings reveal that traditional state-centric security models are insufficient for managing the complex, transboundary threats posed by the Anthropocene. Instead, the research highlights the necessity of reconceptualizing security to include environmental, human, and ecological dimensions, and underscores the importance of cross-border cooperation and integrated governance mechanisms. The analysis demonstrates that a holistic, multidisciplinary approach is essential to effectively address the multidimensional security challenges of this new epoch. The article recommends a paradigm shift in international relations towards more comprehensive and cooperative security strategies that recognize the interconnectedness of human and environmental systems. Such an approach is vital for building global resilience and ensuring sustainable development in the face of the unprecedented challenges of the Anthropocene.